2013
DOI: 10.1080/12460125.2013.841397
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual data model to enhance SKU management in food SMEs

Abstract: This paper reports on an action research project (two-cycle approach -problem solving cycle and research cycle) that investigated the role of data management in supporting product variety/Stock Keeping Unit (SKU) management in a food SME (Small and Medium Enterprise). We find that the SME did not view data as a key resource and hence data redundancy and data integrity issues were fundamental problems. Application of a conceptual data model instilled discipline with regard to data management and this resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This required specific problem solving cycles (e.g. SKU labelling conventions, data cleaning and building a relational database), indeed this learning prompted a subsequent study and this is reported in Sammon and O'Reilly (2013). Hence both practitioners and scholars benefited from iterative cycles which in turn provided the impetus for further initiative.…”
mentioning
confidence: 99%
“…This required specific problem solving cycles (e.g. SKU labelling conventions, data cleaning and building a relational database), indeed this learning prompted a subsequent study and this is reported in Sammon and O'Reilly (2013). Hence both practitioners and scholars benefited from iterative cycles which in turn provided the impetus for further initiative.…”
mentioning
confidence: 99%